Incidencia de la violencia física en la población LGBT en Ecuador. (2018)
Inter-gender violence is a phenomenon that in recent years has become visible in Latin America, however, and unlike the developed countries, the region has no studies on this reality and instruments to improve it. Consequently, the objective of this paper is to find the determinants of physical violence in Ecuador through a broad survey of lesbian, gay, bisexual and transgender (LGBT) groups. The results show that 50% of survey respondents have been assaulted, focusing on transsexuals with low educational level being the most affected. Likewise, the quantitative analysis finds differences between regions, races and reference group (homosexuals, bisexuals, transsexuals, transgender), however, it also highlights the advances that Ecuadorian society has made in this regard. It is concluded that strategies that increase the inclusion of the population of all gender within the opportunities presented to the state will contribute to the reduction of violent tendencies between groups